An Exploratory Analysis of Maternal Health Variables Increasing the Severity of Congenital Heart Disease in Infants. Issue 4 (October 2022) - Butler, Mary
Abstract : Background: Congenital heart defects (CHD) are the most prevalent birth anomaly and leading cause of infant morbidity and mortality worldwide. Heart defects are often attributed to chromosomal abnormality or environmental factors, but most causes remain unknown. The purpose of this analysis was to explore maternal health variables and the relationships to birth outcomes in infants with CHD. Methods: Secondary analysis of data from the Wisconsin Pediatric Cardiac Registry. Results: Maternal history of CHDs (odds ratio [OR] = 2.38; 95% confidence interval [CI], 1.42-3.98) and serious health conditions (OR = 1.537; 95%: CI, 1.08-2.17) increase infant risk and CHD severity. Maternal history of hypertension, serious health conditions, CHD, obesity, and income were predictors of birth weight ( R² = 0.049, P < .05). Maternal history of hypertension, influenza, serious health conditions, and housing were predictors of gestational age ( R 2 = 0.045, P < .05). Birth weight (BW) and gestational age (GA) did not correlate to the severity of CHD in this study (simple vs complex, BW = −0.014, GA = 0.011, r ). Discussion: Maternal well-being influences the health of infants born with CHD. Positive maternal health contributes to near-normal birth weight and gestational age. Conclusion: Nurses must discuss optimal reproductive life planning strategies for decreasing risk of CHD and other infant disorders.